"It may also have prevented churchgoers from falling asleep": southernwood, Artemisia abrotanum L. (fam. Asteraceae), in the church bouquet, and its contemporary presence as a heritage plant in Sweden - Ingvar Svanberg; Erik de Vahl (BMC, 2020)
Abstract Introduction Southernwood, Artemisia abrotanum L., is a plant that has been cultivated for centuries. Most probable is that it has its origin in the eastern Mediterranean area. It has been kept for its fragrance and has a history of being a medicinal and insect-repellent plant. In earlier centuries, the plant was commonly found in peasants' gardens in Sweden and utilised especially as a component in the bouquets brought to church by women. The aim of this article is to bring together data about Artemisia abrotanum and to summarise its cultural history and folk botanical importance. In Sweden, it is still grown in some gardens in the countryside and is esteemed for its fragrance. Methods In the early twentieth century, various folklore archives in Sweden (Lund, Uppsala) distributed questionnaires about the use of church bouquets. These records provided interesting information about the importance of southernwood and other species. We have also used data found in ethnographic records and local historical reports. Between 2007 and 2017, a nationwide inventory organised by the Programme for Diversity of Cultivated Plants (POM) documented and gathered several heirloom varieties of southernwood. Results and discussion Together with a few other domestic plants of foreign origin (e.g. Lavandula angustifolia Mill., Tanacetum balsamita L., and Tanacetum vulgare L.), Artemisia abrotanum has been cultivated throughout Sweden in peasants' gardens as a medicinal plant and for its fragrance. According to the sources, Artemisia abrotanum was one of the most common species cultivated by the Swedish peasantry. Although used in folk medicine and to some extent as a repellent, it was most esteemed for its fragrance. Peasant women would carry a twig of the plant in the obligatory church bouquet or in the hymnal when attending the services in the Lutheran church on Sundays. In Sweden, this custom with the church bouquet has been known since the time of the Reformation in the sixteenth century and survived until the late nineteenth century, when major changes took place in connection with industrialisation, modernisation, secularisation and urbanisation. Although the custom with the church bouquet disappeared, nationwide inventories conducted by the Programme for Diversity of Cultivated Plants in 2007-2015 revealed that the plant still exists in many gardens on the countryside throughout Sweden as a cultural relict and reminiscence plants. People care for the plant, have sentiments for it and it is spread from person-to-person. Several heirloom varieties have been discovered, which will be preserved ex situ for the future. Conclusions Southernwood was probably the most commonly used herb in the peasant women's church bouquet until the end of the nineteenth century. It had a satisfying fragrance and was easy to grow. Although the custom has disappeared, the plant has survived until the present day in many gardens as a reminiscence of the custom of former times.